Creating and Supporting Best Practices in Student Retention - N. Douglas Lees (Academic Chairpersons Conference Proceedings, 2015)
This session will outline motivations/incentives for chairs to participate in, create and support programs that enhance student retention. In addition, from IUPUI, several campus level programs and three department level initiatives, all of which have been shown to be effective in retaining students, will be described.
Keywords: Retention; learning communities; on-campus work; experiential learning; peer mentoring